Influence of Polyfluorinated Side Chains and Soft-Template Method on the Surface Morphologies and Hydrophobic Properties of Electrodeposited Films from Fluorene Bridged Dicarbazole Monomers - Possetto, David Ivan (2023)
A clear case of relationship between the monomer molecular structure and the capability of tuning the morphology of electrodeposited gas bubbles template polymer thin films is shown. To this end, a series of fluorene-bridged dicarbazole derivatives containing either linear or terminally branched polyfluorinated side chains connected to the fluorene subunit were synthesized and their electrochemical properties were investigated. The new compounds underwent electrochemical polymerization over indium tin oxide electrodes to give hydrophobic films with nanostructural and morphological properties strongly dependent on the nature of the side chains. Gas bubbles templated electropolymerization was next achieved by the addition of tiny amounts of water to the monomer solutions, without using surfactants. Within the investigated set of molecules, the nanostructural properties of the soft-templated films obtained from monomers bearing linear side chains could be fine-tuned by adjusting electrochemical parameters, leading to superhydrophobic surfaces.